(untitled) (Memorias Sifored - Encuentros Educación UAN, 2022)
Environmental problems generated by human irrationalities require generations to commit to caring for natural resources and the common home that is the Earth. Therefore, one of the great learnings left by the COVID 19 pandemic is how through educational settings social responsibility can be promoted in terms of caring for the Earth and natural resources, all by strengthening education environmental, as a way to build culture and awareness of care in the face of the imminent need to preserve the environment. For that, it was proposed to start with the formation of habits of caring for the environment from early childhood and hand in hand with family nuclei, such as those models of learning in childhood. As a methodology, the research is based on a qualitative, descriptive approach, and exploratory workshops and participant observation were implemented as data collection techniques.